PENGELOLAAN SINGKONG MENJADI KRIPIK MANGGLENG SEBAGAI PRODUK KREATIF UNGGULAN DESA DUSUN WONODADI DESA ARANG LIMBUNG KABUPATEN KUBU RAYA - Ryani Yulian; Heni Dwi Jayanti (Universitas Muhammadiyah Pontianak, 2018)
The development of agricultural diversification of natural resources as product of creative economy can be the catalyst of economic development. As one of the largest commodities of Dusun Wonodadi Desa Arang Limbung Kabupaten Kubu Raya, cassava is solely sold and distributed as raw commodity. People have low awareness to improve the value of raw material due to less exposure of the creative ideas of producing creative economy product. Concerning this matter, entrepreneurship training in terms of producing creative economy product is essential in order to give added value to cassava. As a result, the society was facilitated to produce ‘kripik manggleng’ as the creative product made from cassava. It is expected that this empowering program can encourage the creative activity of the society in order to boost the spirit of entrepreneurial which can improve the level of their economy.